2016
DOI: 10.1111/ctr.12792
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bisphosphonate therapy in kidney transplant recipients: a systematic review and meta‐analysis

Abstract: Mineral and bone disorders that precede kidney transplantation are exacerbated in the post-transplant setting by tertiary hyperparathyroidism and immunosuppressive regimens. Bone mineral density (BMD) decreases following transplantation, leading to increased fracture risk. The effect of bisphosphonates on fracture is unknown. The aim of this study was to update estimates of change in BMD and fracture rates in bisphosphonate-treated kidney transplant recipients through meta-analysis. Studies comparing bisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
1
12
0
1
Order By: Relevance
“…Bisphosphonates are generally not recommended in patients with eGFR <35 mL/min or evidence of adynamic bone disease due to avoiding over-suppression of bone remodeling. In KT recipients, bisphosphonates have efficacy in improving femoral neck and lumbar spine BMD [ 128 , 129 , 130 ]. Denosumab can be safely administered to CKD-associated osteoporosis, but its side effect of hypocalcemia should be cautious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphosphonates are generally not recommended in patients with eGFR <35 mL/min or evidence of adynamic bone disease due to avoiding over-suppression of bone remodeling. In KT recipients, bisphosphonates have efficacy in improving femoral neck and lumbar spine BMD [ 128 , 129 , 130 ]. Denosumab can be safely administered to CKD-associated osteoporosis, but its side effect of hypocalcemia should be cautious.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD-MBD undergoing HD, ibandronate significantly increased BMD and decreased bone turnover [ 127 ]. In KT recipients, meta-analyses confirmed that bisphosphonates improved the femoral neck and lumbar spine BMD [ 128 , 129 , 130 ], but their effects on fracture risk and safety among KT recipients are not established [ 128 ].…”
Section: Management Of Chronic Kidney Disease-mineral and Bone Dismentioning
confidence: 99%
“…However, among KTRs, bisphosphonates have largely demonstrated improvements in BMD without notable changes in fracture risk. Kan et al conducted a systematic review that noted an improvement solely in lumbar spine BMD ( 151 ), while the review performed by Toth-Manikowski et al demonstrated an association with improved lumbar spine BMD, as well as femoral BMD ( 152 ). Unfortunately, proof of improvement in clinical events is lacking from these reviews and trials.…”
Section: Treatmentmentioning
confidence: 99%
“…There was an increase of around 3 % in both femoral neck and lumbar spine BMD, and an overall reduction in fractures, but no significant reduction in vertebral fractures. Two recent meta‐analyses re‐examined this question in 2016 and both confirmed the results of earlier studies, showing improved BMD at the femoral neck and lumbar spine; however, there no difference in fracture incidence . Adynamic bone disease remains a concern with the use of bisphosphonates.…”
Section: Introductionmentioning
confidence: 68%